World Wide Web - Cloud Boundaries - Kumar, Saroj; Kumar, Santosh (International Journal of Computer Sciences and Engineering, 2019)
In the present post-industrial information epoch where the regular changing environment is depend upon technological abbreviations. Early world was related information with only joining two computers to each other, upto this secure cloud computing policies. Present world races are in racing mode where everyone want to become a leader. Today’s world war is based on information. Information is based on privacy concern over Assess, Compliance, Storage, Monitoring and privacy breaches. Over this phenomena world decide many rules and regulations as per their feasibility to provide information over cloud that still world is in need of better policies over geographical boundaries and country based political issues. Many major rules and regulation are define in this paper to maintain worldwide cloud boundaries for use of fast safe and secure.